2006
DOI: 10.1186/1471-2261-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of modifiable risk factors of heart disease among patients with acute myocardial infarction in Karachi, Pakistan: a cross sectional study

Abstract: Background: Knowledge is an important pre-requisite for implementing both primary as well as secondary preventive strategies for cardiovascular disease (CVD). There are no estimates of the level of knowledge of risk factor of heart disease in patients with CVD. We estimated the level of knowledge of modifiable risk factors and determined the factors associated with good level of knowledge among patients presenting with their first acute myocardial infarction (AMI) in a tertiary care hospital in Karachi, Pakist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
53
7
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 28 publications
(37 reference statements)
20
53
7
5
Order By: Relevance
“…This study exhibited that most of the respondents were able to recognize fatty food consumption, tobacco consumption, lack of exercise and obesity as the risk factors of CHD which is consistent with the study done in Karachi, Pakistan where majority of the respondents knew smoking and fatty food consumption as risk factors (Khan et al;2006). However, the results regarding lack of exercise and obesity is not congruous with the above study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This study exhibited that most of the respondents were able to recognize fatty food consumption, tobacco consumption, lack of exercise and obesity as the risk factors of CHD which is consistent with the study done in Karachi, Pakistan where majority of the respondents knew smoking and fatty food consumption as risk factors (Khan et al;2006). However, the results regarding lack of exercise and obesity is not congruous with the above study.…”
Section: Discussionsupporting
confidence: 67%
“…In a study conducted in Karachi, Pakistan, it was reported that only 4.3 % of the study subjects were involved in exercise (Khan et al;2006). Similarly, another study by (Khadka,2012) in Kathmandu revealed that 17.35% of the total study participants were involved in regular exercise.…”
Section: Discussionmentioning
confidence: 99%
“…No obstante, al explorar el conocimiento específico de cada uno de los factores, un porcentaje similar no logró identificar más de tres factores de riesgo para ECV. Este resultado coincide con otros reportes internacionales (23,24) y pudiera explicarse con base a que la mayoría de los participantes tenían bajo ESE y mínimo nivel de instrucción. Investigaciones previas han evidenciado que el grado de conocimiento de los factores de riesgo cardiovascular está fuertemente asociado al ESE (25).…”
Section: Discussionunclassified
“…En una investigación realizada en Pakistán los individuos estudiados identificaron como factores de riesgo al estrés, HTA, sobrepeso y sedentarismo (26), mientras que en el presente trabajo los factores identificados con mayor frecuencia fueron la grasa dietaria y el hábito tabáquico, en semejanza a lo reportado en Canadá y en otro estudio paquistaní (6,24). Dicho patrón de conocimiento pudiera deberse a que las campañas de prevención para ECV profundizan en la erradicación del hábito tabáquico y en la disminución del consumo de grasas saturadas.…”
Section: Discussionunclassified
See 1 more Smart Citation